(untitled) (Global Journal of Human-Social Science, 2015)
The purpose of this study was to investigate the correlate of psychosocial factors on marital satisfaction among public servant in Cross River State, Nigeria. To achieve the aim of this study psychosocial factors was formed in a lack of affection which lead to depression and low sexual activities or conflict between couples; affecting their marital relationship in the lack of communication, time spent together and on issues of child-rearing. Base on this two null hypotheses were formulated -whether psychological factors (depression, affection and sexual activities) has any relationship to marital satisfaction and if there is any significant relationship between social factors (number of children, communication and time spent together) and marital satisfaction. Literature review was carried out accordingly. Ex-post facto research was adopted for the study. The selection was done through the stratified and simple random sampling techniques. Questionnaire was the main instrument for data collection.